2022
DOI: 10.1007/s40121-022-00746-1
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on CMV Management in Solid Organ Transplant Patients: Prevention, Treatment, and Management of Resistant/Refractory Disease

Abstract: Cytomegalovirus (CMV) infection can have both direct and indirect effects after solid-organ transplantation, with a significant impact on transplant outcomes. Prevention strategies decrease the risk of CMV disease, although CMV still occurs in up to 50% of high-risk patients. Ganciclovir (GCV) and valganciclovir (VGCV) are the main drugs currently used for preventing and treating CMV. Emerging data suggest that letermovir is as effective as VGCV with fewer hematological side effects. Refractory and resistant C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Letermovir, in contrast, was not associated with myelosuppression in the current study or previously among the HCT population . Other antiviral agents used for treatment of CMV disease in recipients of solid organ transplant, including foscarnet and cidofovir, are not realistic prevention alternatives due to the need for intravenous dosing and severe adverse events, including nephrotoxicity . Finally, letermovir has been reported to have a low barrier to resistance when used for active CMV infection; case reports have described the rapid development of letermovir resistance when used to treat resistant or refractory CMV disease .…”
mentioning
confidence: 50%
“…Letermovir, in contrast, was not associated with myelosuppression in the current study or previously among the HCT population . Other antiviral agents used for treatment of CMV disease in recipients of solid organ transplant, including foscarnet and cidofovir, are not realistic prevention alternatives due to the need for intravenous dosing and severe adverse events, including nephrotoxicity . Finally, letermovir has been reported to have a low barrier to resistance when used for active CMV infection; case reports have described the rapid development of letermovir resistance when used to treat resistant or refractory CMV disease .…”
mentioning
confidence: 50%
“…Using an enzyme‐linked immunospot (ELISpot) assay, we observed that the numbers of the secreted IFN‐ γ spots were significantly more when the stimulated CTLs responding to T2 cells loaded with six individually predicted neoantigens (peptide SI, AP1G1, UGT2B10, TPST1, OR2G2, and TGIF2LX) compared to DMSO ( Figure A,B). Three previously validated peptides, cytomegalovirus (peptide CMV), [ 32 ] virus‐associated antigen (peptide HCV: NS3), [ 33 ] and HCC‐associated antigen (peptide VEGFR2‐190), [ 34 ] were recruited as positive control peptides. We also detected the immunogenicity of other candidate neoantigen peptides, and most of them did not show significant differences compared to the control group (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Letermovir, a selective terminase inhibitor, is a new anti-CMV drug that inhibits the formation and release of viral particles and has a lower rate of myelotoxicity. It was previously approved for prophylaxis in hemopoietic stem cell transplant (HSCT) patients [ 16 ]. A review of the literature showed that IgG4-related oesophageal disease with cytomegalovirus infection is very rare.…”
Section: Introductionmentioning
confidence: 99%